Avaliação clínica da relação entre periodontite apical e diabetes tipo 2 : um estudo piloto - Stys, Liliane Preto Agostoni (2020)
Type 2 Diabetes Mellitus (T2DM) is one of the most prevalent chronic non-communicable metabolic diseases. Metabolic disorders and dental infections have common mechanisms in the development of the chronic inflammatory state. This pilot study aimed to investigate the relationship between T2DM and apical periodontitis (AP), through the assessment of endodontic conditions and glycemic control of patients, correlating these parameters with serum levels of inflammatory markers. The study was approved by the Research Ethics Committee (Protocol Number 1,323,531). Thirty patients were divided into 4 groups: H - patients without any of the diseases; AP- patients with AP and without T2DM; T2DM - patients without AP and with T2DM and, T2DM-AP - patients with AP and T2DM. Blood levels of HbA1c were assessed using an immunoturbidimetric method. Serum levels of pro-inflammatory cytokines, interleukin-1β (IL-1β) and interleukin-6 (IL-6), of anti-inflammatory cytokine IL-10, in addition to the chemokines CCL3 and CCL4, were measured using DuoSet kits ELISA sandwich. The lesion area was assessed using the ImageJ program, based on periapical radiographs. The body mass index (BMI) was calculated according to the self-report of weight and height by participants. The results were analyzed by one-way analysis of variance (ANOVA) or Kruskal-Wallis, with Tukey or Dunn post-hoc, for data with and without normal distribution, respectively. Frequency data were analyzed using the chi-square test for linear trend. The level of significance was set at 5%. Most patients diagnosed with T2DM used metformin and antihypertensive medication. The BMI was significantly higher in the T2DM group without AP (p <0.05), compared to the H group. H1bAc was significantly higher in the individuals allocated in the T2DM group, compared to the H and AP groups. (p <0.05; p <0.01, respectively). On the other hand, the T2DM-AP group showed no significant difference in this parameter. The evaluation of serum cytokines showed undetectable levels of IL-6 in all groups evaluated. IL-1β and IL-10 were identified in the serum of some patients,regardless of the experimental group. The same was observed for chemokines, CCL3, and CCL4, which can be associated with other comorbidities in these patients. The areas of the periapical lesion were significantly larger in the T2DM-AP group when compared to the AP group (p <0.05). Studies with larger sample groups are needed to conclude the relationship between AP and T2DM. However, the preliminary results of the present study allow us to infer that either this association is not positive, or the use of metformin may be masking these data.